BENTUK PAKAIAN ADAT BUNDO KANDUANG DI BATIPUAH BARUAH TANAH DATAR - Srimutia Elpalina; Agustina Agustina; Christanto Syam; Adek Cerah Kurnia Azis; Fitrah Cyntha Dirna; Yudhistira Oscar Olendo (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
Clothing can be categorized into several types, such as everyday wear, workwear, festive attire, and traditional costumes. Everyday wear is used for daily activities at home or in society. Workwear is worn when someone is working, like teacher's attire or office clothing. Festive attire is specifically for celebration events, such as birthdays or weddings. On the other hand, traditional costumes are worn during customary ceremonies and hold sacred values. The traditional costume of